PERKEMBANGAN PEMIKIRAN SAID NURSI DARI TAHUN 1876 KE TAHUN 1960 - , SALIH ALBAY ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This work examines develompment of Nursiâs thought. The most essential motto in Nursiâs life is âmusbet hareketâ This motto may be transleted as âNursiâs anti violence and his positivismeâ. Thought of Nursi composed of three principle in the âmuspet hareketâ perspective. Those are to watch harmony and safety of social life